Integración de sectores Atuntaqui y Andrade Marín mediante un equipamiento arquitectónico utilizando criterios de sutura urbana - Pozo Reyes, Stefany Johana (2023)
This work focuses on the theme of urban suturing in a space fragmented by a border path in the city of Atuntaqui-Andrade Marín, specifically on the E35 highway. This border has given rise to a series of everyday situations that affect both residents and visitors of the area. The approach of this study is based on the methodology of urban-architectural design process developed by authors Morella Briceño Ávila and Luz Gómez Rosales, which encompasses the macro, meso, and micro scales. Through the conducted diagnosis, important results have been identified at each of these scales. At the macro level, the relevance of the connection and resonance that the equipment will have in the canton is highlighted. At the meso scale, the mobility of the immediate context has been analyzed to propose a reorganization of the site's actors, including pedestrians and vehicles. Lastly, at the micro scale, lots and distances have been considered to determine suitable locations for the equipment, taking into account their function and available space. As part of the urban suturing proposal, the creation of a commercial food gallery is suggested, accompanied by an urban design that ensures safety at the crossing for the residents and visitors of the place.